The evolution and maintenance of cooperation between unrelated individuals: integrating ultimate and proximate questions - (:unkn) unknown (My University, 2025)
In recent years, new theoretical concepts and empirical research greatly increased our understanding concerning the evolution and persistence of cooperative behaviour between unrelated individuals. We now need to complement the evolutionary knowledge with research about the cognitive and the physiological mechanisms underlying cooperative behaviour. We intend to link evolution and mechanisms in a study on fish cleaning mutualisms. More than 70 species of so called “cleaners” are known to remove ectoparasites but also mucus and scales from so called “clients”. We will use the diversity of cleaner species for a comparative approach, where we will first identify differences between species with respect to dependency on cleaning for their diet, foraging preferences (ectoparasites or mucus), or the probability of repeated interactions with the same clients. We will then explore whether differences in these parameters are linked to potential differences in a) how clients reduce mucus feeding by cleaners, b) variation in the cleaners’ social cognitive abilities, and c) the effects of endocrine substances on cooperative behaviour. The necessary methods have already largely been developed in studies on the cleaner wrasse Labroides dimidiatus, using partly real clients and partly Plexiglas plates as surrogates. We will first determine the endocrine modulators of cooperative behaviour in L. dimidiatus, amenable for further testing in the comparative approach. In addition, we will study the clients’ physiological and immune responses in cleaning interactions. Finally, we will study the potential link between interspecific social competence and body condition as a correlate of the cleaners’ reproductive success. The proposed study is unique with its emphasis on the comparative approach and with the in-depth investigation of the mechanisms underlying cooperative behaviour in a non-human animal. The empirical progress will strongly be enhanced through diverse collaborations with theoreticians, aimed at developing both specific game theoretic models and a more general framework on cooperation between unrelated individuals.
Keywords: mutualism; game theory; cooperation; behavioural endocrinology; marine cleaning mutualism